Unveiling the complexity of cardiac amyloidosis: a comprehensive case report - L. V., Kalatsei; Patel, Krushikumar Panishkumar; Nimavat, Anmol Manish; Reshani, Navindika; Katuwanaarachvhi, Methmi (International Journal of Research in Medical Sciences, 2024)
This case report documents a woman in her sixties who initially presented with cardiac symptoms such as heart palpitations, shortness of breath, and fluctuating blood pressure. Following her hospital admission, she received a diagnosis of paroxysmal atrial fibrillation and underwent successful electrical cardioversion. Despite this intervention, her symptoms persisted, necessitating radiofrequency ablation of the Cavo-tricuspid isthmus, which proved to be highly effective. Subsequent diagnostic testing revealed the presence of coronary artery disease, atherosclerotic cardiosclerosis, and mitral valve abnormalities, all of which were managed appropriately. Upon discharge, the patient was prescribed a medication regimen comprising anticoagulants, hypotensive therapy, and statins, which she tolerated well. However, her symptoms deteriorated, leading to a referral to a specialized center where she was promptly diagnosed with cardiac amyloidosis (CA) and received appropriate treatment. Adjustments to her treatment plan were made based on this diagnosis, and a cardiac MRI confirmed the presence of amyloidosis. A biopsy of the buccal mucosa further confirmed the presence of AL-amyloidosis based on immunohistochemistry test results. The patient commenced chemotherapy, which unfortunately led to kidney damage but ultimately resulted in significant improvement in her condition. Recurrent atrial fibrillation episodes necessitated further interventions, which were performed swiftly and effectively. Multi-organ assessments revealed numerous abnormalities, guiding tailored management strategies. A multidisciplinary team comprising cardiology, hematology, and general practice specialists coordinated the patient’s care, focusing on pharmacotherapy and lifestyle modifications, which were found to be highly effective. Emphasis was placed on continuous monitoring and adherence to treatment plans for long-term management, resulting in positive outcomes.